Kinase gene fusions in defined subsets of melanoma. (January 2017) - Turner, Jacqueline; Couts, Kasey; Sheren, Jamie; Saichaemchan, Siriwimon; Ariyawutyakorn, Witthawat; Avolio, Izabela; Cabral, Ethan; Glogowska, Magdelena; Amato, Carol; Robinson, Steven; Hintzsche, Jennifer; Applegate, Allison; et al.
Summary: Genomic rearrangements resulting in activating kinase fusions have been increasingly described in a number of cancers including malignant melanoma, but their frequency in specific melanoma subtypes has not been reported. We used break‐apart fluorescence in situ hybridization (FISH) to identify genomic rearrangements in tissues from 59 patients with various types of malignant melanoma including acral lentiginous, mucosal, superficial spreading, and nodular. We identified four genomic rearrangements involving the genes BRAF, RET, and ROS1 . Of these, three were confirmed by Immunohistochemistry (IHC) or sequencing and one was found to be an ARMC10‐BRAF fusion that has not been previously reported in melanoma. These fusions occurred in different subtypes of melanoma but all in tumors lacking known driver mutations. Our data suggest gene fusions are more common than previously thought and should be further explored particularly in melanomas lacking known driver mutations.